Development E-Commerce Web Site - Lilyana, Fitria; Tahmat, Tahmat; Rijayana, Iwan (Adpebi International Journal of Multidisciplinary Sciences, 2022)
Buying and selling activities carried out electronically have now become delightful activities for many people. Also called online shopping, this is considered to make it easier for sellers and buyers and seems more practical. Not only making online shops in various types of shopping applications, but many business actors also create e-commerce-themed websites to expand their sales network of products and services. For website creation, many templates can be used, one of which is Prestashop Content Management System (CMS), which is an e-commerce platform used to build online store sites. In Prestashop, there are already many features that can be used, and it also makes it easier for users to build the website they want to create. Even though many people have switched to online shop users. But there are too many shops or malls that they still visit directly to see first-hand the quality of the desired goods.